Surgical Exposure Gained in an Extended Retrosigmoid Approach to the Cerebellopontine Angle Compared to the Traditional Retrosigmoid Approach - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2014)
AIM: Retrosigmoid approach to the posterior fossa has been a popular and dependable approach for accessing the cerebellopontine angle (CPA) and petroclival region. Although this approach is commonly used, it requires cerebellar retraction and has limitations when the lesion is located ventral to the brainstem. The aim was to quantify the angle of view provided by extended retrosigmoid approach in comparison to the traditional approach. A secondary objective was to identify a strategic initial burr hole site for craniotomy. MATERIAL and METHODS: Ten adult human cadaver heads (20 sides) were used. First, traditional retrosigmoid approach was performed and the angle of exposure was measured on cranial computerized tomography (CT). Following, extended retrosigmoid approach was performed with mastoid bone drilling and reflection of venous sinuses. Angle of exposure was measured on CT. Two measurements of both approaches were compared. RESULTS: Mean angle of view for the traditional retrosigmoid approach (31.4 degrees +/- 4.1 degrees) was significantly smaller than that of the extended approach (46.0 degrees +/- 4.7 degrees) (p<0.001). Site of strategic burr hole was 5 mm below and 15 mm lateral to the asterion was defined. CONCLUSION: Extended retrosigmoid approach offers neurosurgeons approximately 50% larger angle of view and shorter working distance than the traditional approach provides. This modification permits better access to the CPA and ventral brain stem without cerebellar retraction.
Keywords: Cerebellopontine angle; Extended retrosigmoid approach; Retrosigmoid approach; POSTERIOR-FOSSA; INFRATENTORIAL APPROACH; PETROSAL APPROACH; SURFACE; SUPRATENTORIAL; ANEURYSMS; LESIONS